The depth of the stromal invasion of cutaneous squamous cell carcinoma in correlation with tumor size and tumor differentiation - Kakasheva-Mazhenkovska, Lena; Janevska, Vesna; Basheska, Neli; Kostadinova Kunovska, Slavica; Jovanovikj, Rubens; Mitevska, Elida (Macedonian Association of Pathology, 2016)
Objective: The aim of this study was to determine the correlations between stromal invasion and the grade of differentiation as well as tumor’s size in squamous cell carcinoma of the skin (SCC). Material and Methods: Surgically resected skin specimens from 30 patients with cutaneous SCC, were included in the study. The hematoxylin-eosin stained histological sections containing the tumor tissue and the surrounding normal skin prepared from routinely processed paraffin blocks were analyzed by light microscopy. In each analyzed SCC, the degree of histological differentiation (G) and the postoperative tumor status (pT) of the neoplasm according to TNM classification (AJCC) were determined. The depth of stromal invasion in each case was measured on low power field (x40) using morphometry software. The distance from the basement membrane of the epidermis to the deepest invasive neoplastic focus of the tumor and the obtained values are presented in absolute numbers expressed in micrometers. Results: The SCC in 21 (70%) cases was classified as pT1 and in 9 (30%) cases as pT2 category tumor. Twelve tumors (40%) were classified as well (G1), 13 (43.3%) as moderately (G2), and 5 (16.7%) as poorly (G3) differentiated tumors. The depth of stromal invasion was ranging from 1561.2 μm to 13000.1 μm. A statistically significant difference was found between the depth of invasion in tumors belonging to different pT category (Mann-Whitney U test, p=0.003034 for pT1 and pT2), and different grade (Kruskal-Wallis test, p=0.00008 for G1, G2, G3). Conclusions: The depth of stromal invasion was higher in larger SCCs with a maximal diameter greater than 2 cm (pT2) and in poorly differentiated (G3) tumors.
Keywords: skin; squamous cell carcinoma; tumor size; depth of stromal invasion; grade of differentiation